National culture and small firms' use of trade credit: evidence from Europe - Moro, Andrea; Belghitar, Yacine; Mateus, Cesario (Elsevier, 2021)
We examine the use of trade credit in Western Europe by relying on a sample of 182,296 small firms for the period 2003–2013. Building on information asymmetry theory, we explore how a country's culture can impact SMEs use of trade credit. We discover that countries' cultural norms play a key role in explaining trade credit differences in Europe. We find that in countries with high power distance, high individualism, high masculinity, and high uncertainty avoidance rely more on trade credit.
Keywords: Trade credit; Culture; SMEs; Bank credit; Financial flexibility